Shortening of Platelet Survival by Induced Hypercholesterolaemia In Rabbits and Its Prolongation by Anagrelide - Barrett, P A; Butler, K D (Thrombosis and Haemostasis, 1983)
Induction of atherosclerosis in rabbits by feeding a cholesterol enriched diet reduced the platelet half-life in male rabbits from 37.0 ± 4.1 hr to 30.1 ± 3.9 hr (mean ± S.D. p ≤0.01). Platelets from these animals exhibited increased sensitivity to arachidonic acid but decreased sensitivity to ADP. No significant change was found in aggregation to collagen or thrombin, or in the production of thomboxane B2 induced by collagen.The reduced platelet survival was dependent upon the recipient animal and not the platelet donor. Platelets from cholesterol- fed animals survived normally in normal animals, whereas platelets from normal animals in cholesterol-fed animals had a reduced platelet survival even compared to platelets from cholesterol-fed animals. This might suggest that some functional change had occurred in the cholesterol platelet in response to its altered environment.Anagrelide (1 mg/kg/day) normalised shortened platelet survival in both male and female rabbits fed the high cholesterol diet.
Keywords: Heparin; Other mucopolysaccharides; Anticoagulation; Mode of action